Restoring of Destroyed Primary Incisors Using Two Different Techniques: Clinical Study - Nourallah, Abdul Wahab; Ibrahim, Seba (Latakia University Journal -Medical Sciences Series, 2019)
Aim: To evaluate the effectiveness of composite post in restoring destroyed primary incisors compared to glass fiber post. Material and Methods: The study sample consisted of 36 destroyed maxillary primary incisors in 11 children aged between (2-5) years. After endodontic treatment, the incisors were allocated into two groups for restoration with intra canal posts (n= 18 in each group): group A ( glass fiber posts) and group B (composite posts). The restorations were clinically followed-up at 3, 6, 9, and 12 months post treatment for retention and marginal integrity. Results: After 12 months of treatment, the retention rates were 94.12% in group A and 70.59% in group B, and the marginal integrity rates were 93.75% in group A and 100% in group B. The differences between the two groups regarding the two criteria were statistically insignificant. Conclusion: The glass fiber post technique showed the higher retention rate, whereas the composite post technique showed the higher marginal integrity rate. However, both techniques were successful and could be used in restoring destroyed primary incisors. الهدف: تقييم فعالية وتد الكومبوزيت في ترميم القواطع المؤقتة المتهدمة بالمقارنة مع وتد الألياف الزجاجية. المواد والطرائق: تألفت عينة الدراسة من 36 قاطعة علوية مؤقتة متهدمة لدى 11 طفلاً تراوحت أعمارهم بين (2-5) سنوات. تمَّ توزيع القواطع بعد اجراء المعالجة اللبية لها على مجموعتين للترميم مع أوتاد قنيوية (N= 18 في كل مجموعة): المجموعة A ( مجموعة وتد الألياف الزجاجية) والمجموعة B (مجموعة وتد الكومبوزيت). تمّت متابعة الحالات سريرياً بعد 3 و6 و9 و12 شهراً، وتمَّ التقييم من حيث ثبات الترميمات وسلامة حوافها. النتائج: بلغ معدّل ثبات الترميمات بعد 12 شهراً 94.12% في المجموعة A و70.59% في المجموعة B، كما قد بلغ معدّل سلامة الحواف 93.75% في المجموعة A و100% في المجموعة B بعد 12 شهراً من المعالجة، ولم يكن الفرق بين المجموعتين في كلا المعيارين مهمّاً إحصائياً. الاستنتاج: حققت تقنية وتد الألياف الزجاجية معدّل ثبات أعلى من تقنية وتد الكومبوزيت، بينما حققت تقنية وتد الكومبوزيت معدّل سلامة حواف أعلى مع ذلك كانت المعدّلات مرتفعة في كلا التقنيتين وبالتالي يمكن اعتماد أي منهما في ترميم القواطع المؤقتة المتهدمة.